Influência da freqüência da corrente alternada da nitretação a plasma nas propriedades superficiais do aço inoxidável ASTM F138 - Silva, Edilaine Honorio da (Universidade Federal de São Carlos, 2013)
Plasma nitriding is a technique which is used in surface treatments of stainless steel, in order to improve some properties like hardness, wear and corrosion resistance. The nitrided layer consists of some iron nitrides: the cubic y´ phase (Fe4N), the hexagonal yphase (Fe2-3N) and a nitrogen supersatured solid phase yN. Moreover, the phases which are formed and their amount are related to the nitriding parameters: time, temperature, gas mixture (N2/H2) and pressure. On the other hand, the equipment used in this study can be operated using AC or DC current. If the AC current is used, its frequency can vary and possibly influence the Fe-N phase formation as well. In order to study this influence, some ASTM F138 stainless steel disks, showing 19,00 ± 0,01 mm diameter and 2,00 ± 0,01 mm thickness, were plasma nitrided for 4h, at 400ºC, in a 80%H2 - N2 gas mixture, at a pressure of 6 Torr, using AC current, at 6, 12, 30, 60 e 100 kHz. The samples were characterized using Scanning Electron Microscopy, Magnetic Force Microscopy, X Ray Diffraction, Hardness Vickers and Mössbauer Spectroscopy. X Ray Diffractions results detected peaks of yN phase for all samples, which showed higher hardness when compared with matrix. Nitrided layer thickness seems not to be influenced by frequency, except for 12kHz, which produced a layer whose thickness (approximately 8 ym) was about 40% thicker than the average for the other samples. Magnetic Force Microscopy showed that nitrided layer is magnetic near the surface and is paramagnetic in the innermost layer near the matrix. Mössbauer Spectroscopy demonstrated the presence of the yN, yand y´ phases. Moreover, it showed that, although the most superficial region seems to be essentially magnetic, there is also a small contribution of paramagnetic phases. Finally, the samples which were nitrided using 12 kHz showed the best results.
Keywords: Superfícies (Física); Nitretação a plasma; Espectroscopia de Mossbauer; Raios-X - difração; Aço inoxidável; Filmes finos superfícies; CIENCIAS EXATAS E DA TERRA::FISICA